A Note on the 1947 Input-Output Study - Bailey, William R. (The Review of Economics and Statistics, 1968)
[1] Haavelmo, Trygve: Comment on Leontief, Wassily, Rates of Long-Run Economic Growth and Capital Transfer from Developed to Underdeveloped Areas, Study Week on The Econometric Approach to Development Planning (October 7-13, 1963), Pontificiae Academiae Scientiarvm Scripts Varia, (Amsterdam: North-Holland Publishing Company, 1965). [2] Chenery, Hollis and Alan M. Strout, Assistance and Economic Development, American Economic Review, 56, no. 4 (Sept. 1966), 679-733. [3] Rahman, Md. Anisur: Welfare Economics of Foreign Aid, Pakistan Development Review, Summer, 1967.